Can China's land coupon program activate rural assets? An empirical investigation of program characteristics and results of Chongqing. (January 2017) - Wen, Lan-jiao; Butsic, Van; Stapp, Jared R.; Zhang, An-lu
Abstract: Harmonizing land use across space to optimize residential and agricultural land uses is an issue in many developed and developing countries. China, where the state has strong property rights, has developed its own set of policies to address this problem. One of the most common policies is the land coupon, a scheme where rural residential lands are reclaimed to farmland, and equivalent amounts of farmland located in urban regions are converted to construction (residential, industrial, or commercial) land. The scheme aims to preserve the total amount of farmland within a region, while also allowing cities to add commercial and residential buildings on former farmland. The purpose of this paper is to introduce an English speaking audience to the land coupon program in Chongqing, describe its characteristics, and finally investigate in depth the efficacy of the program to activate rural assets. Choosing Chongqing as our study area, we use a price gradient model to estimate the gap between prices compensated to rural residents for their residential land and the price of the land coupons at auction. We also compare the compensation to urban farmland owners, and rents to urban commercial land. The results indicate that 1) The average price gradient between supply (1.71 thousand yuan/m 2 ) and demand regions (3.14 thousand yuan/m 2 ) indicates that there is still a large land value gap between regions; 2) the scarcity degree—the amount of excess land in a city region that can be converted to agriculture—is a significant predictor of coupon price in both supply and demand areas; and 3) scarcity degree usually has an impact on price, negatively in supply regions, but in demand regions, there is a U-shaped relationship between price difference and scarcity degree. Highlights: Land coupons are a policy to harmonize urban and rural land markets. Land coupons promote no net loss of farmland. Urban rents remain higher than prices paid to rural landowners in land coupon markets.